The association between playgroup participation, learning competence and social-emotional wellbeing for children aged 4-5 years in Australia - Nicholson, J; Hancock, K; Berthelsen, D; Zarb, D; Lawrence, D; Mitrou, F; Zubrick, S (My University, 2011)
Playgroups are regular gatherings of parents and children aged less than 5 years. Over $9 million of annual funding is contributed towards playgroups, yet little is known about the extent to which playgroups achieve their objective of improving the wellbeing of children and families. This study uses data from Growing Up in Australia: The Longitudinal Study of Australian Children to examine the associations between playgroup participation and the outcomes for children aged 4 to 5 years. Controlling for a range of socio-economic characteristics, playgroup participation across the ages of 0-3 years was used to predict learning competence and social-emotional functioning at age 4-5 years. For learning competence, children from disadvantaged families scored 3-4% higher if they attended playgroup when they were aged 0-1 and 2-3 years compared to children from disadvantaged families who did not attend playgroup. For social-emotional functioning, girls from disadvantaged families who attended playgroup when they were aged 0-1 and 2-3 years scored nearly 5% higher than those who did not attend. Demographic characteristics also showed that disadvantaged families were the families least likely to access playgroups. This study provides evidence that continued participation in playgroups is associated with better outcomes for children from disadvantaged families.
Keywords: Education and Training; Child Development; Education and Training -- Early Childhood; Childhood and child development; Learning, education and training; Education and Training; Child Development; Early Childhood; Childhood and child development; Learning, education and training